2004
DOI: 10.1111/j.1464-410x.2004.04882.x
|View full text |Cite
|
Sign up to set email alerts
|

Holmium:YAG laser vaporization of recurrent papillary tumours of the bladder under local anaesthesia

Abstract: OBJECTIVESTo evaluate holmium:YAG laser vaporization of papillary tumours of the bladder, focusing on surgical technique, patients’ satisfaction, complications and cost‐effectiveness when using the technique under local anaesthesia as an outpatient procedure.PATIENTS AND METHODSIn all, 52 consecutive patients with recurrent papillary tumours of the bladder were scheduled for holmium:YAG laser vaporization under local anaesthesia using a flexible cystoscope. The number of papillomas and total operative duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 10 publications
2
21
0
2
Order By: Relevance
“…A survey study of holmium:YAG vaporization as daysurgery management concluded that, though the initial costs of the technology are high, the long-term value is cost effective after only a few procedures [77]. Wong et al [78] offered office-based laser ablation (OLA) in place of inpatient cystodiathermy (IC) to 54 frail elderly patients (mean age 77 years, more than half with at least three comorbidities).…”
Section: Office-based Laser Ablation For Frail Elderly Patientsmentioning
confidence: 99%
“…A survey study of holmium:YAG vaporization as daysurgery management concluded that, though the initial costs of the technology are high, the long-term value is cost effective after only a few procedures [77]. Wong et al [78] offered office-based laser ablation (OLA) in place of inpatient cystodiathermy (IC) to 54 frail elderly patients (mean age 77 years, more than half with at least three comorbidities).…”
Section: Office-based Laser Ablation For Frail Elderly Patientsmentioning
confidence: 99%
“…Its efficacy was proven in stone treatment and indications have been extended to urethral strictures and ureterocele. Application of the holmium laser in soft tissues includes bladder tumors and prostatic tissue ablation, performing tumor fulguration by a continued pulse starting at 1-1.4 J, 10-14 Hz frequency, and a depth of 0.4-0.6 mm [10] . With the knowledge of its use to treat vascularized lesions, we used the holmium laser technique in our patient for total removal of the hemangiomas and achieved a good tolerance, absence of adverse events and no postoperative complications.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, patients would prefer to avoid general anesthesia and the concomitant discomfort if sufficient alternatives are offered. In a study by Jonler et al [2] laser treatment was used for treatment of recurrent papillary bladder tumors with the sole use of local lignocaine gel. All patients stated that they would undergo the same treatment again if necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Male sex and pre-operative dependency in daily living were major risk factors for decreased five-year survival [1]. It has recently been argued that intravesical local anaesthetic infiltration is a feasible option for pain elimination in patients undergoing resection of superficial bladder tumors [2][3][4]. However, suprapubic pain and lower urinary tract symptoms often mandate the use of post-operative analgesic regimens.…”
Section: Introductionmentioning
confidence: 99%